Harapan dan Kenyataan: Implementasi Kurikulum Pendidikan Inklusi di Sekolah Dasar Negeri: Kota Bandung - Ginting, Seriwati; Darmayanti, Tessa Eka; Wianto, Elizabeth; Yuwono, Astrid Austranti (Ideas Publishing, 2025)
The background of the research examines the factors that cause the incompatibility of government regulations with real conditions in the field related to inclusive education. The methods used are qualitative descriptive and analyze documents, regulations applied in public elementary schools in the city of Bandung and explore the perception of teachers, students, parents and education staff. The purpose of the study is to find the compatibility between the rules and the implementation of inclusive education that focuses on equity, equal opportunities for all students from diverse backgrounds. The results of the study still have a sharp gap between rules and real conditions such as the student admission process, curriculum, assessment system, teacher availability, and facilities needed.